Boom–bust cycles and asset market participation waves: Momentum, value, risk, and herding - Roberto Dieci; Noemi Schmitt; Frank Westerhoff (Journal of Evolutionary Economics, 2025)
We develop an asset market participation model in which investors base their market entry decisions on the momentum, value and risk of the market. Despite our behavioral framework, the model's fundamental steady state is characterized by standard present-value relations between expected future payouts and the model-implied risk-adjusted return. We derive conditions under which endogenous asset market participation waves and co-evolving boom–bust cycles emerge. Moreover, we show that the asset market may display spontaneous, sharp, and permanent downturns if investors react sensitively to risk, an outcome that goes hand in hand with low asset market participation rates and excess volatility.
Keywords: D84; G12; G41; 330; Boom–bust cycles; Asset market participation waves; Momentum; Value and risk; Herding behavior; Feedback loops